HBR Case Studies: Making Change Stick (Harvard Business Review Case Studies) - Authors (Harvard Business Press, 2008)
Companies today are forced to transform almost continuously--leaving managers faced with difficult questions. How soon can you initiate change as a new hire? Should you merge cultures after an acquisition? How can you create lasting results when the majority of change efforts fail?